2016
DOI: 10.7771/1541-5015.1580
|View full text |Cite
|
Sign up to set email alerts
|

The Empathy Project: Using a Project-Based Learning Assignment to Increase First-Year College Students’ Comfort with Interdisciplinarity

Abstract: IntroductionOur university is diverse in a number of ways, including the more traditional categories of race, ethnicity, religion, and socioeconomics. This contributes positively to students' intellectual and emotional development, and adds quality and depth to discussions in class. The University's academic and political diversity are also important assets and encourage interdisciplinary courses to truly span departments and to promote the critical thinking of our students. Part of the University's commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 15 publications
0
14
0
2
Order By: Relevance
“…A previous study by Hutchison [7] found projectbased learning was an effective instructional strategy for teaching empathy for college students in the interdisciplinary context. Project-based learning is an instructional model of inquiry-based learning and is rooted in constructivism which asserts knowledge and comprehension are constructed by the learner and are built upon his or her past experience [8].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A previous study by Hutchison [7] found projectbased learning was an effective instructional strategy for teaching empathy for college students in the interdisciplinary context. Project-based learning is an instructional model of inquiry-based learning and is rooted in constructivism which asserts knowledge and comprehension are constructed by the learner and are built upon his or her past experience [8].…”
Section: Introductionmentioning
confidence: 98%
“…Project-based learning is an instructional model of inquiry-based learning and is rooted in constructivism which asserts knowledge and comprehension are constructed by the learner and are built upon his or her past experience [8]. Although research indicates project-based learning is effective in developing student empathy [7], little is known about using this instructional strategy to teach empathy to medical students. Thus, this study presents a project-based learning approach to develop empathy in entry-level medical students.…”
Section: Introductionmentioning
confidence: 99%
“…Embora a pesquisa de Self e Baek (2017) ter demonstrado que os alunos podem não perceber a eficácia da aprendizagem em equipe, a empatia gerada entre discentes a partir de projetos interdisciplinares foi captada por Hutchison (2016). Esses projetos permitiram aos alunos melhorar as habilidades básicas da comunicação, escrita e oral, raciocínio ético e quantitativo e pensamento crítico.…”
Section: Introductionunclassified
“…Project-based learning (PBL) can provide great opportunities for students to enhance their engineering understanding and skills [12][13][14][15][16][17]. Students can not only gain theoretical knowledge from lectures, but also obtain valuable hands-on experience in real-world project practice, where they can actively improve their abilities in self-motivated learning, self-efficacy beliefs [15], problem solving, adaptation to interdisciplinary thinking and collaborative learning [16].…”
Section: Introductionmentioning
confidence: 99%
“…Students can not only gain theoretical knowledge from lectures, but also obtain valuable hands-on experience in real-world project practice, where they can actively improve their abilities in self-motivated learning, self-efficacy beliefs [15], problem solving, adaptation to interdisciplinary thinking and collaborative learning [16]. The PBL approach also helps with improving the achievement of low-performing students [17].…”
Section: Introductionmentioning
confidence: 99%